PENERAPAN METODE DEMONTRASI UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR - Elli Handayani (DIADIK, 2022)
This study aims to describe the application of the demonstration method to increase creativity and student achievement. The research that was conducted was Classroom Action Research and continued with quasi-experimental research. Classroom Action Research was carried out in three cycles, each cycle going through the stages of planning, implementation, observation and reflection. The research subjects were sixth grade students of SD Negeri 2 Merapi Timur Lahat. The instruments used are observation sheets and test sheets. The technique of collecting data was by observing and testing, while the experimental class only tested the demonstration method. Data analysis was carried out using the t test and the classical mean value. Based on the data analysis of this study, it was concluded that (1) the application of the demonstration method could increase students' creativity; (2) The application of the demonstration method can improve student achievement; (3) There is an effective use of the demonstration method to improve student achievement in science subjects for class VI at SD Negeri 2 Merapi Timur Lahat